Global dispersal and diversification of the genus Schoenus (Cyperaceae) from the Western Australian biodiversity hotspot. Issue 4 (1st June 2021) - Elliott, Tammy L.; van Mazijk, Ruan; Barrett, Russell L.; Bruhl, Jeremy J.; Joly, Simon; Muthaphuli, Ngalirendwe; Wilson, Karen L.; Muasya, A. Muthama
Abstract: The predominantly austral genus Schoenus L. is the largest genus in tribe Schoeneae and one of the ten most species‐rich Cyperaceae genera, with over 150 accepted species found mostly in Australia, New Zealand, southeast Asia, and southern Africa. Here, we use data based on two nuclear and three plastid DNA regions to present one of the most comprehensive phylogenetic reconstructions of a genus in Cyperaceae to date, covering over 70% of described species of Schoenus . After recent taxonomic realignments in the last 4 years have both added and removed species from the genus, we show that Schoenus is now monophyletic. In addition, our results indicate that Schoenus originated in Western Australia in the Paleocene and eventually dispersed to surrounding continents, but rarely back. The diversification rate of the genus appears to have slightly decreased over time, and there has not been an increase associated with the establishment of the Cape clade endemic to the sclerophyllous fynbos vegetation type, such as has been reported in other plant lineages endemic to the Cape region. These results will serve as a template to understanding the complex patterns of genome size evolution and to untangle drivers of diversification in this genus.